Pendekatan Manajemen Pendidikan Islam Dalam Mewujudkan Budaya Sekolah Berbasis Multikulturalisme - Tiara Indria Ningrum (Jurnal Dinamika Pendidikan Islam, 2025)
This study examines the implementation of Islamic educational management in building a multicultural school culture in an era of diversity. The background of the study is the challenge faced by Islamic educational institutions in responding to the socio-cultural pluralism of Indonesian society. The purpose of this research is to analyze Islamic educational management strategies in creating an inclusive school environment that respects diversity. The study employs a qualitative approach with a case study conducted in three madrasahs in Indonesia. Data were collected through in-depth interviews, observations, and documentation. The findings indicate that the application of Islamic values of rahmatan lil ‘alamin, transformational leadership, an integrated curriculum, and stakeholder participation are key factors in achieving success. The conclusion emphasizes that Islamic educational management is effective in realizing a multicultural school culture through the harmonization of universal Islamic values with principles of tolerance and mutual respect.